“Recursos audiovisuales para la enseñanza y aprendizaje en el área de lengua y literatura” - Cajilema Lema, Karina Elizabeth (2022)
Learning in each individual is different and education as a comprehensive training process relies on different means to ensure the consolidation of knowledge and this implies that teaching practice must be updated and adapted to new teaching scenarios. The teacher as a guide of the students faces an important challenge related to the updating of methodologies adapted to the generations that develop in a knowledge society closely immersed in new technologies and communication media. The mastery of technological tools is not yet a strength for the teaching staff, since the design and elaboration of audiovisual resources is still an unusual practice in educational institutions despite having appropriate technologic equipment for their creation and production. This project proposes to promote the use of audiovisual resources elaborated with Filmora tools to strengthen the teaching and learning of students in the area of Language and Literature. This study was consolidated with the elaboration of audiovisual resources, for which qualitative research, interpretive approach and descriptive and bibliographic study procedures were applied, inductive method because it allowed executing of a process with particular premises to later consolidate it in a general analysis. The results obtained showed that the application of audiovisual media as part of the teaching-learning process allows consolidating a more solid way the new learning related to language and literature, especially because it the strengthens the communicative macro-skills through visual-auditory elements that capture interest and maximize concentration time. The development of audiovisual resources in this project is important to the extent that its implementation shows a very evident impact on the way of adjusting to different learning styles and above all because it promotes the use of communication technologies for an education that integrate the technological equipment and tools as allies of quality education.